Fermentative Production of N-Methylglutamate From Glycerol by Recombinant Pseudomonas putida - Mindt, Melanie; Walter, Tatjana; Risse, Joe Max; Wendisch, Volker F. (Frontiers in Bioengineering and Biotechnology, 2018)
N-methylated amino acids are present in diverse biological molecules in bacteria, archaea and eukaryotes. There is an increasing interest in this molecular class of alkylated amino acids by the pharmaceutical and chemical industries. N-alkylated amino acids have desired functions such as higher proteolytic stability, enhanced membrane-permeability and longer peptide half-lives, which are important for the design of new peptide-based drugs, the so-called peptidomimetics. Chemical synthesis of N-methylated amino acids often is limited by incomplete stereoselectivity, over-alkylation or the use of hazardous chemicals. Here, we describe metabolic engineering of Pseudomonas putida KT2440 for the fermentative production of N-methylglutamate from simple carbon sources and monomethylamine. P. putida KT2440, which is generally recognized as safe and grows with glucose and the alternative feedstock glycerol as sole carbon and energy source, was engineered for the production of N-methylglutamate using heterologous enzymes from Methylobacterium extorquens. About 3.9 g L-1 N-methylglutamate accumulated within 48 h in shake flask cultures with minimal medium containing monomethylamine and glycerol. A fed-batch cultivation process yielded in a N-methylglutamate titer of 17.9 g L-1.